Physics over easy : breakfasts with Beth and physics - Azároff, Leonid V. (World Scientific, 1996)
In easy-to-follow conversational language, this book reveals the mysteries of physics and tells about the physicists who made it possible, from the discovery of the laws of gravity by Isaac Newton and the construction of the first electric battery by Alessandro Volta, to the present century's development of solid-state electronics, nuclear arms and nuclear reactors, lasers, etc. The evolution of physics during four centuries is related in sixteen conversations that actually took place between the author, a professor of physics, and his wife, an intelligent listener not familiar with the subjec.